The Relationship Between Students’ Knowledge, Peer Roles, Teacher Roles, and Bullying Behavior at SMK YPI Tanjung Bintang - Febriani, Christin Angelina; Arisandi, Syafik; Susanti, Fitri Aprilia (Universitas Airlangga, 2025)
Background: Emotional instability in adolescents can trigger problems such as bullying which is now back to being an issue of violence in schools. Bullying can take place directly or online, bullying can have dangerous impacts. In addition to physical consequences, bullying can also trigger mental and emotional health problems. The report of the Lampung Province PPPA Service recorded a total of 296 cases, with the highest number in Bandar Lampung City with 94 cases and South Lampung Regency in second place with 47 cases. Objectives: The purpose of this study was to determine the determinants of bullying behavior in students at SMK YPI Tanjung Bintang. Method: This type of research is quantitative with a cross-sectional approach. The population in this study were active students at SMK YPI Tanjung Bintang and a sample of 117 respondents selected using purposive sampling techniques, and using questionnaires. Data analysis used the chi square test with a significance level of 95%. Results: The study showed that there was a relationship between knowledge and bullying behavior (p value 0.001; OR = 19,282), the role of peers with bullying behavior (p value 0.001; OR = 17,405), the role of teachers with bullying behavior (p value 0.001; OR = 22,000). The researcher's suggestion is that the school can create a TPPK (Violence Prevention and Handling Team) task force and the school can improve routine anti-bullying education and integrate the material into the curriculum either directly or through extracurricular activities. Keywords: Bullying Behavior, Knowledge, Role of peers, Role of teachers